The impact of insecticide-treated material to reduce flies among pork outlets in Kampala, Uganda - Heilmann, Martin; Roesel, Kristina; Grace, Delia; Bauer, B.; Clausen, Peter-Henning (Springer, 2017)
Synanthropic flies have adapted to the mass of decaying organic matter near human settlements. As such, they feed and breed on food, faeces and other organic material and are known vectors for various diseases. Many of these diseases are associated with food, and foodborne diseases are of growing concern in developing countries where human population and food consumption increase. This pilot study aims at investigating the impact of a novel application of insecticide-treated material (ZeroFly®) to reduce flies among pork outlets in Kampala, Uganda. A cross-sectional survey randomly selected 60 of 179 pork outlets in Kampala. A controlled longitudinal trial followed in which 23 out of the 60 pork outlets were recruited for an intervention with insecticide-treated material. The pork outlets were randomly allocated to a group of 18 netted pork outlets (intervention) and five non-netted pork outlets (control). Monitoring took place over 15 weeks including 2 weeks as the baseline survey. The units were monitored for fly abundance using non-attractant sticky traps, which were placed within the pork outlet once per week for 48 consecutive hours. Medians of fly numbers before and after the intervention indicated a decrease of fly numbers of 48% (p = 0.002). Fly bioassays showed that the insecticidal activity of the netting remained active over the entire intervention period and led to a total paralysis of flies within at least 6 h after exposure. Insecticide-treated material provides a practical and sustainable solution in controlling flies and is therefore recommended as a complementary strategy for an integrated vector control and hygiene management.